Modificações na morfologia, anatomia e fisiologia de Typha domingensis Pers. em função do alto adensamento populacional - Scarpa, Ana Lívia Martins (2017)
The aim of the work was to verify the occurrence of changes in the biometric, anatomical and physiological characteristics of Typha domingensis Pers. (Typhaceae) in populations with different natural densities. Plants were sampled on natural populations showing high or low density and submitted to biometric, anatomical and physiological evaluations. The experimental design was completely randomized with two treatments and 15 replicates. Data were submitted to analysis of variance and were compared by the Scott-Knott test for p <0.05. Populations under high densification showed smaller spacing, greater density of plants and leaf area. The values stomatal conductance and total a reduction of the radiation intensity grow, suffered a reduction of the macronutrient and micronutrients content, as well nutrient uptake by plants. Therefore, T. domingensis under high density condition showed increased leaf area and total photosynthesis leading to the production of a larger number of clones. Plants of high density populations developed adaptations in the bundles to overcome a higher need of water, nutrients and photoassimilates, as well as aerenchyma development. The high density population of T. domingensis affects the microclimate and the soil where the populations grow, reducing the radiation intensity and the availability of macro and micronutrients.